Mobility prospects and preferences for redistribution in Latin America - Lasarga, Evelin (2022)
The present paper aims to provide evidence about the POUM hypothesis (prospects of upward mobility) in Latin America. It postulates that preferences for redistribution decrease with the prospects of upward mobility of individuals, given that in a possible economic improvement they would be harmed by redistribution. The case of Latin America is analyzed for the period 2009-2018, which has registered changes in inequality and intragenerational mobility in part, due to redistributive policies in the past decade. For this, data from Latinobarómetro and the Probit-Adapted OLS methodology are used. The results support the POUM hypothesis, unlike what the studies carried out for previous periods obtain, in another context of inequality and mobility in Latin America. In addition, suggestive results are obtained about the influence of intergenerational mobility, religiosity, ideology and institutional quality on preferences for redistribution. It should be noted that these results vary according to the country.